Crocin Prevents Patulin‐Induced Acute Toxicity in Cardiac Tissues via the Regulation of Oxidative Damage and Apoptosis. Issue 10 (11th June 2015) - Boussabbeh, Manel; Ben Salem, Intidhar; Neffati, Fadwa; Najjar, Mohamed Fadhel; Bacha, Hassen; Abid‐Essefi, Salwa
ABSTRACT Patulin (PAT) is a mycotoxin produced by several species of the genera of Penicillium, Aspergillus, and Byssochlamys principally by Penicillium expansum. This mycotoxin is suspected to affect several organs including kidney and liver. However, its toxic effect on heart remains unknown. The present study investigated for the first time the cardiotoxic effect of PAT in mice. We demonstrated that PAT increased creatinin phosphokinase (CPK) level, induced lipoperoxydation and protein oxidation, and triggered the antioxidant enzymes such as superoxide dismutase and catalase activities. We also demonstrated that acute administration of PAT triggers apoptosis via P53 overexpression and caspase 3 activation. We further investigated the antioxidant efficiency of crocin (CRO), a carotenoid pigment, against PAT‐induced cardiotoxicity. We found that pretreatment with CRO prevents cardiac impairment by reducing CPK levels, restoring the redox statute and suppressing apoptosis. Collectively, our data provide new preventive effect of CRO toward PAT‐induced cardiotoxicity in mice.